Analisis Hukum Perdata Atas Klaim Perpanjangan Waktu (Extension Of Time/Eot) Dan Kompensasi Biaya Dalam Kontrak Konstruksi: Perspektif Wanprestasi, Overmacht, Dan Hardship - Agus Prasetio; Sami’an Sami’an; Sarwono Hadjomuldjadi; Ganis Vitayanty Noor (Syntax Corporation, 2026)
Delays in work execution are one of the most dominant sources of disputes in construction contracts. Within the framework of Indonesian civil law, delays are conventionally positioned as a form of breach of contract that results in compensation and contractual sanctions. However, this approach is often inadequate to explain delays in construction projects, which are complex, multi-causal, and influenced by various external factors. Modern construction contract practice responds to this condition through Extension of Time (EOT) mechanisms and cost compensation as contract adjustment instruments. This article aims to analyze the status of EOT claims and cost compensation from an Indonesian civil law perspective using a doctrinal approach to the concepts of breach of contract, overmacht, and hardship. This research is a normative legal study with statutory, conceptual, and comparative approaches. The results of the study indicate that EOT claims and cost compensation cannot be understood narrowly as exceptions to breach of contract, but rather as corrective mechanisms that function to maintain contractual balance. The integration of the doctrines of breach of contract, overmacht, and hardship allows for the creation of a more proportional, adaptive, and equitable legal approach in modern construction contracts..